Multiyear Tracking of Nassau Grouper Spawning Migrations. Issue 1 (28th October 2016) - Dahlgren, C. P.; Buch, K.; Rechisky, E.; Hixon, M. A.
Abstract: An understanding of temporal patterns of migration and spatial connectivity between home ranges and spawning sites is necessary for effective management of species that form transient spawning aggregations. The Nassau Grouper Epinephelus striatus is a Caribbean coral reef fish that displays such spawning aggregations, which have been overfished to the point of threatening the species. Using acoustic telemetry, we examined the size at which Nassau Grouper migrate to spawning aggregations, the timing of migrations, and the distance of migration routes used by Nassau Grouper from within and outside of a large, no‐take marine reserve in the central Bahamas. Fish (total n = 19) were tagged in 2004 ( n = 6) and 2005 ( n = 13) and were tracked for one to four spawning seasons. Fish that were 54 cm TL or greater made spawning migrations, with all but one migrating southward along the shelf edge of Exuma Sound for a distance of 70 km to over 200 km, usually during the December full moon. Fish typically made one migration annually, which lasted from 1 to 3 weeks, with fish remaining at spawning sites for only 1–2 d; however, when the full moon was early in the spawning season, several fish remained away from their home reefs through two lunar cycles or delayed their migrations by a month, and one fish made two migrations. Fish that were migrating for the first time had slower swimming speeds to spawning sites than did experienced fish, but swimming speeds were similar between the two groups during return migrations, suggesting that their migration behavior was learned. Our results demonstrate that spawning migration patterns for this species may be more variable in The Bahamas than at other Caribbean locations. The present findings also have important implications for the management of the species, including increasing the minimum size limit to 54 cm or larger and the use of both marine protected areas and seasonal closures to rebuild the spawning stock. Received February 1, 2016; accepted July 27, 2016